Swim Like a Fish! Integration of Fundamental Movements in Child Literature for Enhancing Early Physical Literacy (Universitas Pendidikan Indonesia, 2025)
Reading has long been recognized as an essential activity to instill values, such as moral value, in children. Physical literacy, as the key factor to a child lifelong physical activity, becomes one of the potential vital values to be nurtured through reading activities. However, there has not been any child book targeting early physical literacy. Therefore, this research aimed to compile a story book for children, aged 4-6 years, specifically designed to enhance physical literacy by integrating fundamental movements in the storyline, including the locomotor, non-locomotor, and manipulative movements. This study was conducted in design-based research method framework which includes five procedures, namely need analysis, planning, product design development, testing, and revision stages. Results of expert judgment and user reviews showed that the draft of the book was suitable for use after revision. A substantial revision had been made to the draft based on the suggestions given by experts and users/practitioners and rated as suitable. This research has successfully produced a story book for children in two languages, Indonesian and English languages. The book has integrated suitable fundamental movements and been provided with pictures and illustrations to be used in reading activities. This book is expected to help children enhance early Physical Literacy in a fun way and suitable with their development stages.